Tribological response of soft materials sliding against hard surface textures at various numbers of cycles. (20th June 2012) - Menezes, Pradeep L.; Kishore,; Kailas, Satish V.; Lovell, Michael R.; Souza, Roberto M.; de, Daniel
ABSTRACT In the present investigation, various kinds of textures were attained on the steel surfaces. Roughness of the textures was varied using different grits of emery papers or polishing powders. Pins made of pure Al, Al–4 Mg alloy and pure Mg were then slid against prepared steel plate surfaces at various numbers of cycles using an inclined pin‐on‐plate sliding tester. Tests were conducted at a sliding velocity of 2 mm s−1 in ambient conditions under both dry and lubricated conditions. Normal loads were increased up to 110 N during the tests. The morphologies of the worn surfaces of the pins and the formation of transfer layer on the counter surfaces were observed using a scanning electron microscope. Surface roughness parameters of the plate were measured using an optical profilometer. In the experiments, it was observed that the coefficient of friction and formation of a transfer layer (under dry and lubricated conditions) only depended on surface texture during the first few sliding cycles. The steady‐state variation in the coefficient of friction under both dry and lubrication conditions was attributed to the self‐organisation of texture of the surfaces at the interface during sliding. Copyright © 2012 John Wiley & Sons, Ltd.